Smart rogaining for computer science orientation - Chessa, Manuela; Delzanno, Giorgio; Ferrando, Angelo; Gelati, Luca; Guerrini, Giovanna; Mascardi, Viviana; Noceti, Nicoletta; Odone, Francesca; Vitali, Francesca (Frontiers in Education, 2022)
In this paper, we address the problem of designing new formats of computer science orientation activities to be offered during high school students internships in Computer Science Bachelor degrees. In order to cover a wide range of computer science topics as well to deal with soft skills and gender gap issues, we propose a teamwork format, called smart rogaining, that offer engaging introductory activities to prospective students in a series of checkpoints dislocated along the different stages of a rogaine. The format is supported by a smart mobile and web application. Our proposal is aimed at stimulating the interest of participants in different areas of computer science and at improving digital and soft skills of participants and, as a side effect, of staff members (instructors and university students). In the paper, we introduce the proposed format and discuss our experience in the editions organized at the University of Genoa before the COVID-19 pandemic (2019 and 2020 waves).